A Mixed-Methods Study to Investigate Barriers and Enablers to Nurses' Implementation of Nonpharmacological Interventions for Infants With Neonatal Abstinence Syndrome. (December 2020) - Adrian, Allison; Newman, Susan; Mueller, Martina; Phillips, Shannon
Abstract : Background: The incidence of neonatal abstinence syndrome has increased significantly as a result of the opioid epidemic. A lengthy hospitalization is often required to treat the infant's withdrawal symptoms. A comprehensive understanding of factors that influence nurses' implementation of nonpharmacological interventions for infants with neonatal abstinence syndrome is needed. Purpose: To investigate barriers and enablers to nurses' implementation of nonpharmacological interventions for infants with neonatal abstinence syndrome through the lens of the Theoretical Domains Framework, which provides a structure to examine factors that influence healthcare providers' behavior related to the implementation of evidence-based practice and interventions in clinical practice. Methods: A convergent parallel mixed-methods study was conducted. Qualitative data were collected using semistructured interviews and quantitative data were collected using a tailored Determinants of Implementation Behavior Questionnaire with neonatal nurses. Findings from the interviews and surveys were merged through joint review to compare and contrast themes. Results: Enablers and barriers to nurses' implementation of nonpharmacological interventions included education, experience, ability to implement nonpharmacological interventions, parental participation, stigmatization, lack of managerial/organizational support, staffing ratios, internal and external resources, and stress. Knowledge, Skills, Beliefs About Capabilities, Social/Professional Role and Identity, Organization, and Emotion of the Theoretical Domains Framework aligned with these themes. Implications for Practice and Research: Findings from this study will inform the development of programs to improve nurses' implementation of nonpharmacological interventions and health and utilization outcomes in infants with neonatal abstinence syndrome. Furthermore, future work should focus on the development of programs to improve nurses' implementation of nonpharmacological interventions, with specific strategies aimed to mitigate marginalization of vulnerable patient populations. Abstract : Supplemental Digital Content is Available in the Text.